PENGARUH PHYSICAL ENVIRONMENT DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA LUAR GARIS COFFEE DI BATAM: customer satisfaction; physical environment; product quality - Fazari, M.hamzah; Saputra, Asron (LPPM Universitas Putera Batam, 2024)
This research aims to examine the influence of the physical environment and product quality on customer satisfaction at Luar Garis Coffee in Batam. The research population consists of customers who visit Luar Garis Coffee, with a sample size of 100 customers who made purchases at the venue. The sampling technique used is non-probability sampling with a purposive sampling method. The sample selection criteria are customers who have shopped at Luar Garis Coffee. Data were collected through the distribution of questionnaires. Data processing was carried out using SPSS v.26. The results of the study indicate that the physical environment has a positive effect on customer satisfaction, whereas product quality does not significantly influence customer satisfaction at Luar Garis Coffee, with an F-test value of 5.763. The T-test results show that the t-value for the physical environment is 3.257 > 1.985 with a significance value of 0.002 < 0.05, which means H1 is accepted, while the t-value for product quality is -1.200 < 1.985 with a significance value of 0.233 > 0.05, which means H2 is rejected.